(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article provides information about nicknames that are being studied as an anthroponymic unit in Uzbek linguistics. The opinions of linguists about nicknames are presented. Considerations have been made regarding the distinction between nicknames and names.